THE IMPLEMENTATION OF MNEMONIC DEVICE BY USING PICTURES TO IMPROVE SEVENTH GRADERS' SHORT FUNCTIONAL TEXTS READING ABILITY - Sunendar, Neidya Fahma (2016)
This study describes an implementation of Mnemonic Device by using pictures as a learning technique to improve seventh graders' short functional texts reading ability. It aims at (1) investigating the implementation of Mnemonic Device as a learning technique in reading short functional texts by seventh graders; (2) gaining the students' responses to the implementation of Mnemonic Device in reading short functional texts. A classroom action research was employed as a research design in this study and it was divided into four phases namely Planning, Acting, Assessing, and Reflecting (as adapted from Kemmis & McTaggart, 1992). The data were collected through several instruments namely: classroom observation, students' assessment, and interview with the students, the data then analyzed by using the theory of qualitative data analysis proposed by Hamied and Malik (2016) while the mean score of the students' tests/assessments were calculated by using frequency distribution suggested by Hasan (2001). The result of the study revealed that Mnemonic Device has successfully improved seventh graders' short functional texts reading ability which can be seen from the mean scores of Pre-test, Test in the First Cycle, and Test in the Second Cycle (from 74.84, 77.10 and 89.32). There were some students' responses regarding to the implementation of Mnemonic Device such as: the students were motivated to read short functional texts correctly and their active participation in the learning activity.